ENHANCING GENERIC SCIENCE SKILLS THROUGH INQUIRY-BASED LEARNING: A FOCUS ON ELECTROLYTE SOLUTIONS IN CHEMISTRY EDUCATION - Meriza Faradilla (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The inquiry-based learning model has been widely recognized for itseffectiveness in enhancing students' science generic skills, particularly in thecontext of chemistry education. This study explores the impact of applying theinquiry learning model on the development of students' generic science skills,specifically in the topic of electrolyte solutions. The research aims to assesshow inquiry-based teaching methods can improve students' abilities inproblem-solving, critical thinking, and practical application of scientificconcepts. The study involved a quasi-experimental design with pre-test andpost-test assessments to measure the students' progress. The results indicate asignificant improvement in the students' generic science skills, suggesting thatthe inquiry model fosters active engagement, deeper understanding, andenhanced scientific inquiry abilities. These findings highlight the potential ofinquiry-based learning as a strategy for improving chemistry education,particularly in topics that require conceptual and practical mastery such aselectrolyte solutions.